2019
DOI: 10.1101/697409
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

64-Channel Carbon Fiber Electrode Arrays for Chronic Electrophysiology

Abstract: A chief goal in neuroscience is to understand how neuronal activity relates to behavior, perception, and cognition. However, monitoring neuronal activity over long periods of time is technically challenging, and limited, in part, by the invasive nature of recording tools. While electrodes allow for recording in freely-behaving animals, they tend to be bulky and stiff, causing damage to the tissue they are implanted in. One solution to this invasiveness problem may be probes that are small enough to fly under t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…A number of electroplating times were tested, and 30 s produced superior signal isolation among the recording sites (Figure 5). While it has been well established that PEDOT-pTS 12 , 24 , 25 , 26 and PEDOT-TFB 21 provide reliable options for preparing carbon fiber recording sites, we found that plating with gold, a proven and dependable method for electroplating electrodes for chronic implantation 27 , 28 , increased the ease of implantation and prevented the electrode tips from clumping together. In producing final impedance values of less than 0.2 MΩ on average, this method proves comparable to values achieved using PEDOT-TFB 21 and PEDOT-pTS 26 .…”
Section: Discussionmentioning
confidence: 83%
“…A number of electroplating times were tested, and 30 s produced superior signal isolation among the recording sites (Figure 5). While it has been well established that PEDOT-pTS 12 , 24 , 25 , 26 and PEDOT-TFB 21 provide reliable options for preparing carbon fiber recording sites, we found that plating with gold, a proven and dependable method for electroplating electrodes for chronic implantation 27 , 28 , increased the ease of implantation and prevented the electrode tips from clumping together. In producing final impedance values of less than 0.2 MΩ on average, this method proves comparable to values achieved using PEDOT-TFB 21 and PEDOT-pTS 26 .…”
Section: Discussionmentioning
confidence: 83%
“…This progressive loss of signal is a major motivation behind our electrode design work, because the only known way to improve signals over the long run is to reduce electrode scale. While carbon fiber electrode arrays have demonstrated stable recordings over long time scales, yield is low and the fabrication process is not scalable [40]. Thin-film silicon carbide ultramicroelectrodes provide a scalable alternative that will be investigated further [41], and polymer electrodes using insertion shuttles show promise for increasing signal longevity [42].…”
Section: Discussionmentioning
confidence: 99%
“…The Maharbiz lab has also developed a higher channel probe that was inserted to depths of 2.5-3 mm [51]. The Cox lab has also developed a carbon fiber bundle probe ~ 1 mm in length [39]. These probe geometries will be of greater use to labs doing chronic work in deeper brain structures.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the many advantages of carbon fibers, many labs find manual fabrication of these arrays to be arduous. Some groups [39] combine carbon fibers into bundles that collectively result in a larger ( ~ 200 μm) diameter than a traditional microwire [39], [40]. Others have fabricated individuated carbon fiber electrode arrays, though their methods require cleanroom-fabricated carbon fiber guides [41]–[43] and equipment to populate their arrays [35], [42], [43].…”
Section: Introductionmentioning
confidence: 99%